THE QUALITY OF POWERPOINT SLIDES MADE BY ENGLISH DEPARTMENT STUDENTS OF PADANG STATE UNIVERSITY IN PRESENTING ENGLISH COURSE MATERIALS - NOVIE ASFIRA; DON NARIUS (Journal of English Language Teaching, 2017)
This research is a descriptive research that is intended to reveal the quality of PowerPoint slides made by English Department of Padang State University in presenting English course materials. The data in this research were obtained from the archives of PowerPoint which is already presented in course TEFL course (Teaching English as Foreign Language) by educational-program students. Up until now, the software which is known as PowerPoint has been widely used to assist the learning process in academic settings ranging from the primary school level to the higher level such as university. Thus, a research on the use of this software academic fields needs to be conducted. The instrument used in this study is an analytic rubric. After conducting the research, the quality of students’ PowerPoint slides in term of the content accuracy was still in average. Since the students were already in the final year, the ability to understand the text about the course materials is expected to be better. Nevertheless, although the final score was considered as an average, there are still some students who presented the course materials incorrectly. In other words, the information they presented was different from the original source given by the instructors.